Mycorrhizal fungi associated with Coccoloba uvifera in Colombian tropical dry forest: an approach for ecological restoration (2022)
The study of mycorrhizal fungi community composition, diversity, and structure is important to understand mechanisms of local dynamics of native forests. Despite their importance and the strong dependency that plant have on these symbiotic fungi, MF are often overlooked in restoration efforts. This study case focuses on Coccoloba uvifera (sea grape), a plant species present in tropical dry forests, which an important floristic element in coastal ecological restoration and commonly propagated in forest nurseries. This species also forms ectomycorrhizal) associations. This research compares the composition and diversity of root-associated fungal communities present in seedlings of C. uvifera growing in natural forest and in a forest nursery with and without natural soil inoculum. To do so the nursery¿s traditional treatment and a native soil modified one were used to grow C. uvifera seedlings and measure them after two and four months of growth. After four months, the entire root system of 32 seedlings was collected for DNA extraction and quantification of mycorrhizal colonization. DNA sequencing was carried out by amplifying the fungal ITS2 region using the Illumina miseq platform. In addition, 19 fruiting bodies of ectomycorrhizal fungi found near the sampled C. uvifera natural populations were collected. Our results showed strong differences in root-associated fungal community composition of seedlings growing in different nursery treatments and natural population. Strikingly, seedling growing in traditional nursery substrates without natural soil inoculum show very little to no colonization of symbiotic fungi in their roots. Preliminary results of seedlings growth rate showed no significant differences in plant between treatments after four months. The characterization of EcM fungal communities associated with of this iconic tropical dry forest tree species allows the improvement of local restauration and conservation efforts. The differences found suggest inoculating seedling could be an effective way of restoring soil microbial communities with plants produced ex-situ for reforestation.